Randomized controlled trial comparing daycare and overnight stay laparoscopic cholecystectomy - Salleh A.A.M.; bin Ariffin A.C.; Hairol O.; Zamri Z.; Azlanudin A.; Hilmi M.A.; Razman J. (Societa Editrice Universo, 2024)
Indexed by SCOPUS/WOS